TRAINING in MAKING INNOVATION INTERACTIVE LEARNING MEDIA FOR TEACHERS of SMAN KARANGPANDAN - Avega Tri Regista Nurrega; Aisyah Mutia Dawis, M.Kom. (The Journal Publishing, 2022)
The background behind the holding of this training is the lack of knowledge about interactive learning media, in addition due to the still pandemic conditions, a teacher who is in Karangpandan high school, is required to be able to continue to provide learning even though it is online. Therefore, a teacher must be able to provide interesting and interactive learning, so that students continue to be interested in learning even though they are online. The number of learning media made using various applications requires every teacher to have an understanding and skills regarding information and communication technology. By understanding information and communication technology correctly, it can make it easier for teachers to create various interesting interactive media, in this training we will use pear-deck and class points. These two applications are perfect for teachers who want to be skilled in making interactive learning media and make teachers more creative and innovative.